2012
DOI: 10.1038/ncomms1633
|View full text |Cite|
|
Sign up to set email alerts
|

Mouse and human strategies identify PTPN14 as a modifier of angiogenesis and hereditary haemorrhagic telangiectasia

Abstract: HHT is a vascular dysplasia syndrome caused by mutations in TGF-β/BMP pathway genes, ENG and ACVRL1. HHT shows considerable variation in clinical manifestations, suggesting environmental and/or genetic modifier effects. Strain-specific penetrance of the vascular phenotypes of Eng+/− and Tgfb1−/− mice provides further support for genetic modification of TGF-β pathway deficits. We previously identified variant genomic loci, including Tgfbm2, which suppress prenatal vascular lethality of Tgfb1−/− mice. Here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 59 publications
3
72
2
1
Order By: Relevance
“…This could be remediated by optimized dosing strategies, but may require the development of new drugs against tissue-specific TGF-b signaling components that are active only on discrete cell types of the TME, such as GARP. Finally, if TGF-b blockade drugs are approved for widespread use, there will be considerable variation in both therapeutic and toxicological responses among patients (Bonyadi et al 1997;Akhurst 2004;Valle et al 2008;Benzinou et al 2012;Chung Kang et al 2013;Kawasaki et al 2014). There is therefore a growing need for development of predictive biomarkers of TGF-b blockade (Gueorguieva et al 2014;Kawasaki et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be remediated by optimized dosing strategies, but may require the development of new drugs against tissue-specific TGF-b signaling components that are active only on discrete cell types of the TME, such as GARP. Finally, if TGF-b blockade drugs are approved for widespread use, there will be considerable variation in both therapeutic and toxicological responses among patients (Bonyadi et al 1997;Akhurst 2004;Valle et al 2008;Benzinou et al 2012;Chung Kang et al 2013;Kawasaki et al 2014). There is therefore a growing need for development of predictive biomarkers of TGF-b blockade (Gueorguieva et al 2014;Kawasaki et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, progress through the clinical pipeline has been slow. It may be that the window between antitumor efficacy and toxicological effects has been considered too narrow for general use, especially considering that genetic variation between individuals helps define the outcomes of germline genetic loss of TGF-b signaling components, and thus might influence both therapeutic drug responses and on-target side effects (Bonyadi et al 1997;Akhurst 2004;Benzinou et al 2012;Chung Kang et al 2013;Kawasaki et al 2014). Taking into account the many activities of TGF-b and its pleiotropic actions, major efforts focus on identifying alternative targets that influence the TGF-b signaling pathway, with a strong incentive to identify drugs that might block TGF-b's tumor progressing activities while sparing tumor-suppressing activities.…”
Section: Future Directions With Tgf-b Blockadementioning
confidence: 99%
“…Similarly, VEGFR3, an LEC marker, is essential for hemangiogenesis, where it can act with or independently of VEGF or VEGFR-2 to activate angiogenesis (9,28). In this respect, it is intriguing that polymorphisms in PTPN14, a gene mutated in a lymphedema syndrome (29), show genetic association with the incidence of arteriovenous malformations in HHT patients (30), suggesting an interaction with endoglin/ALK-1 signaling in vascular development. PTPN14 interacts with VEGFR3 (29) and regulates EphrinB2 expression (30), suggesting further functional interaction between ALK-1 and VEGFR3.…”
mentioning
confidence: 99%
“…In this respect, it is intriguing that polymorphisms in PTPN14, a gene mutated in a lymphedema syndrome (29), show genetic association with the incidence of arteriovenous malformations in HHT patients (30), suggesting an interaction with endoglin/ALK-1 signaling in vascular development. PTPN14 interacts with VEGFR3 (29) and regulates EphrinB2 expression (30), suggesting further functional interaction between ALK-1 and VEGFR3. Direct functional cross-talk between ALK-1-activated Smads and VEGFR3 signaling, possibly complementing ALK-1-Notch signaling cross-talk as seen in hemangiogenesis (31), may additionally coordinate LEC and BEC proliferation and differentiation.…”
mentioning
confidence: 99%
“…PTPN14 overexpression activates TGF-b signalling and causes epithelial-mesenchymal transition (EMT) 2 . Its overexpression is also correlated with lymphatic function, choanal development, angiogenesis and hereditary haemorrhagic telangiectasia 4,5 . Recent studies have revealed that PTPN14 negatively regulates the oncogenic function of Yes-associated protein (YAP) through retaining YAP in the cytoplasm and sustaining the phosphorylation state of YAP [6][7][8][9] .…”
mentioning
confidence: 99%